Exchange rate, Investment, and Industrial Development: Revisiting their role in bringing Economic Growth to Pakistan - Shaheen, Dr. Ruqia; Anwar, Robina; kiran, Sadia; Sarwar, Iqra (The journal of contemporary issues in business and government, 2023)
The goal of this study is to better understand how Pakistan's economic growth is influenced by factors such as investment, industrial development, and exchange rates. From 1974 to 2020, data from Pakistan of various have been used for the analysis. The empirical findings demonstrated a long-term relationship between the variables of the study using the Autoregressive distributed lag (ARDL) model in Pakistan. The performance of economic growth was observed to have a positive correlation with the labor force participation rate, and investments were observed to have a strong positive correlation with economic growth. According to the findings of the study, Pakistan should develop policies that align the exchange rate with the sector's actual demands to boost investment and economic growth. The policy must be based on a comprehensive understanding of both the various industry segments and the broader trends that affect them. According to conventional wisdom, devaluations of the currency are frequently used as development strategies. In the absence of accurate knowledge regarding how exchange rate fluctuations influence the sector and economic growth, policy intervention results in ineffectively low economic growth performance.